CURRENT MANAGEMENT AND EXTERNALITIES IN LOBSTER FISHERIES EXPLOITATION ON THE CONTINENTAL SHELF OF CEARÁ, BRAZIL - Santana, João V. Mendes; Neves, Soraya D. S.; Saraiva, Soniamar Z. R.; Adams, Charles; Cruz, Raul (Arquivos de Ciências do Mar, 2015)
In this study we analyzed the current models of extraction and management of Brazilian spiny lobster resources and looked into the problems caused by different types of associated externalities. The Brazilian continental shelf is not divided into fishing zones, making it impossible to prevent the concentration of fishing vessels and effort. The lobster production and wholesale marketing chain is complex: vessels of varying size and different legal or illegal methods and fishing gear are used, none of which are selective, and a significant part of the production is sold to middlemen who retain a large percent of the profits. In general, fishermen disregard existing regulations on resource use and access. This is equivalent to a regime of nonproperty (open access) in which individuals can directly take possession of resources. Unrestricted access leads to overexploitation of common property, making rational allocation of resources impossible and generating negative externalities.